THE EFFECT OF ISLAMIC ETHIC TO EMPLOYEE'S PRODUCTIVITY IN BANK MUAMALAT INDONESIA PANGKALPINANG - Diah Novianti (Pusat Riset dan Inovasi Nasional, 2022)
Employee performance in this study is focused on performance whose measurement is through work assessment This study aims to determine the effect of islamic ethic to employee’s productivity in Bank Muamalat Indonesia Pangkalpinang. Primary data from questionare become data source for this study and it will be analyze using single linear regression with SPSS 26. This study sample is all of the population totally 28 respondent. Based on the results of the partial test calculation (T test), the tstatistic value is (2.163) < ttable (1.73406) with a significance level of 0.044 > 0.05. This means that it shows that the Islamic Work Ethics variable partially and significantly affects the Productivity of the Employees of Bank Muamalat Indonesia Pangkalpinang Branch